China's Industrial Policy and Electric Vehicle Export Expansion: A Neomercantilism Strategy in the Shift of Global Automotive Industry Power (2020-2025) - Gerald Angelo Pantarego; Indrawati (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
This study analyzes China's New Energy Vehicle (NEV) export expansion (2020–2025) as a neomercantilism strategy within International Political Economy. It argues China's global EV dominance stems from systematic state intervention rather than free markets. This intervention relies on four pillars: (1) strategic industrial policies like Made in China 2025; (2) domestic subsidies exceeding USD 520 billion alongside Dual-Credit mechanisms; (3) vertical control of global supply chains, dominating lithium processing and cobalt mining; and (4) geoeconomic integration through the Belt and Road Initiative. Using a qualitative case study, findings reveal this strategy drove NEV production from 1.37 million units in 2020 to over 16 million in 2025. Consequently, China bypassed Japan as the top automotive exporter in 2023, while BYD captured a 22.2% global market share in 2024. Ultimately, China's NEV expansion functions as a strategic instrument to secure geopolitical interests and realize its ambition as a dominant global economic power